Petrogenesis of Cretaceous shoshonitic rocks in the northern Wuyi Mountains, South China: A result of the roll-back of a flat-slab? - Li, W.; Li, X.; Wang, Xuan-Ce; Yang, D. (Elsevier BV, 2017)
© 2017 Elsevier B.V. Potassic magmatism is commonly linked to post-/late-orogenic environments, such as foundering or convection thinning of continental lithosphere. Their petrogenesis is crucial for constraining the chemical and physical properties of the remnant sub-continental lithospheric mantle. Here we report new SHRIMP zircon U–Pb ages, whole rock geochemical results and Sr–Nd and zircon Hf isotope data from four potassic plutons (the Da'an, Yingcheng, Zixi and Honggong plutons) in the northern Wuyi Mountains, South China. SHRIMP U–Pb zircon analyses indicate that these potassic rocks formed at 139–126 Ma. They are characterized by high SiO 2 (56–73%) and K 2 O (3.8–6.7%), with a K 2 O/Na 2 O ratio of 2.18–2.04, plotting within the field of high-SiO 2 shoshonites. Their I Sr and eNd(t) values vary from 0.7077 to 0.7162 and - 5.66 to - 10.52, respectively. The initial zircon eHf(t) values range from 2.3 to - 13.1, corresponding to T DM modal ages between 707 and 1330 Ma. These geochemical and isotope characteristics indicate that these shoshonites derived from a subduction-modified ancient subcontinental lithospheric mantle, and then underwent significantly fractional crystallization of K-feldspar, plagioclase, and accessory minerals, such as apatite and Fe–Ti oxides during magma ascent. We interpret that asthenospheric mantle upwelling (caused by eastward roll-back of a flat-slab?) triggered partial melting of the metasomatized lithospheric mantle to result in the Early Cretaceous shoshonitic magmatism in the northern Wuyi Mountains. An integration of our new results with compiled data from the interior of the South China Block reveals that the arc-like geochemical signature is confined to the Wuyi Mountains region, but becomes little or even invisible toward inland in South China. This implies that the far-field effects of the early Mesozoic subduction only reached the Wuyi Mountains, ca. 500 km away from the trench, consistent with flat or shallow subduction models.